2012
DOI: 10.7439/ijbar.v3i7.567
|View full text |Cite
|
Sign up to set email alerts
|

Declining Hiv Seroprevalence Among Pregnant Women in South Odisha, India: A Six and Half Year Tertiary Care Hospital Based Study

Abstract: Background: Acquired Immune Deficiency Syndrome (AIDS) caused by Human Immunodeficiency Virus (HIV) has emerged as the greatest threat to human existence. Estimating the rate and trends of HIV seroprevalence among pregnant women provides essential information for an effective implementation of Prevention of Parent to Child Transmission of HIV (PPTCT) programme and for monitoring its spread within different parts of the country. Objective: As few studies are available from India on HIV prevalence among the ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…8 In comparison to other studies of Uttar Pradesh; higher seroprevalence of 0.4% were observed by Mehrotra et 16,20,22 In study done by Gupta et al in AIIMS Delhi, India, prevalence was found to be 0.88%. 21 Studies from south India by Giri 7,15,17,22,27,30 Analyzing the reason for this difference between our results and NACO data, could be different surveillance system. Present study is hospital based survey for past 11 years while NACO uses sentinel surveillance system and being a tertiary centre, most of seropositive HIV women are referred from several centers, so higher number of seropositive antenatal women are attended in our hospital.…”
Section: Dwivedi S Et Al Int J Reprod Contracept Obstet Gynecol 201mentioning
confidence: 81%
See 4 more Smart Citations
“…8 In comparison to other studies of Uttar Pradesh; higher seroprevalence of 0.4% were observed by Mehrotra et 16,20,22 In study done by Gupta et al in AIIMS Delhi, India, prevalence was found to be 0.88%. 21 Studies from south India by Giri 7,15,17,22,27,30 Analyzing the reason for this difference between our results and NACO data, could be different surveillance system. Present study is hospital based survey for past 11 years while NACO uses sentinel surveillance system and being a tertiary centre, most of seropositive HIV women are referred from several centers, so higher number of seropositive antenatal women are attended in our hospital.…”
Section: Dwivedi S Et Al Int J Reprod Contracept Obstet Gynecol 201mentioning
confidence: 81%
“…16 According to present study majority of the women were multigravida and studied up to primary or secondary in contrast to study done by Dash et al and Patil et al where most of the women were primigravida and was either illiterate or studied up to primarylevel. 15,17 In this study, multigravida were found to be more infected as they were more exposed to infection. Whereas Perry et al state that there is no significant difference between seropositive and seronegative women regarding socioeconomic status, residence and religion.…”
mentioning
confidence: 87%
See 3 more Smart Citations